The exhumation rate of Dabie orogen: Evidence from garnet diffusion zoning - Cheng, Hao; Chen, Daogong; Deloule, Etienne (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 116-7